Torang Samua Basudara : Nilai Budaya dalam Menjaga Kerukunan Hidup Beragama di Kota Manado. - Muhammad Kamil Jafar N (Universitas Negeri Medan, 2021)
This article aims to describe and analyze the cultural values of Torang Samua Basudara which are the philosophy of living in harmony in the city of Manado. This study uses qualitative research methods, with data collection techniques namely observation and interviews, data analysis using three stages, namely data collection, reduction, and drawing conclusions. The results of the study provide an overview of the history of the origin of the meeting between ethnic Minahasa and immigrants who show an attitude of openness and care for the Minahasa people, then the core meaning of the torang samua basudara value is that we are all God's creations, must love one another, cherish and live in good conditions, as well as the reality of interpersonal life. religion in the city of Manado shows a harmony in society, differences do not become obstacles but they support each other in the common good.